2014
DOI: 10.1097/mjt.0b013e318230ae7b
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis Induced by Zonisamide

Abstract: Zonisamide is an anti-seizure medication that is indicated for adjunctive therapy in the treatment of partial seizures. This medication is rarely used in the United States. An infrequent adverse effect of psychosis occurs in about 2% of patients taking zonisamide. This is a case report of a 34-year-old male on phenytoin who presented with psychosis symptoms approximately 10 months after starting adjunctive zonisamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Upon literature review, four reported cases were found (Table 1), the median age was 37 (range 30-50), affecting both genders equally, and symptoms started between 1 and 10 months after starting zonisamide. Nevertheless, our patient was similar to the reported cases where symptoms completely resolved after medication discontinuation [8][9][10][11]. In Japan, a retrospective study was done by Miyamoto et al…”
Section: Discussionsupporting
confidence: 90%
“…Upon literature review, four reported cases were found (Table 1), the median age was 37 (range 30-50), affecting both genders equally, and symptoms started between 1 and 10 months after starting zonisamide. Nevertheless, our patient was similar to the reported cases where symptoms completely resolved after medication discontinuation [8][9][10][11]. In Japan, a retrospective study was done by Miyamoto et al…”
Section: Discussionsupporting
confidence: 90%